2023
DOI: 10.1038/s41398-022-02302-4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and replication of blood-based proteomic signature of PTSD in 9/11 responders

Abstract: Proteomics provides an opportunity to develop biomarkers for the early detection and monitoring of post-traumatic stress disorder (PTSD). However, research to date has been limited by small sample sizes and a lack of replication. This study performed Olink Proseek Multiplex Platform profiling of 81 proteins involved in neurological processes in 936 responders to the 9/11 disaster (mean age at blood draw = 55.41 years (SD = 7.93), 94.1% white, all men). Bivariate correlations and elastic net regressions were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Yet, GFAP levels could be significantly reduced in individuals with other neuropathologies specifically because GFAP might be binding directly to the cerebrum thereby avoiding being sloughed into the blood ( Pereira et al, 2021 ). A prior study of WTC responders with PTSD and mild cognitive impairment found downregulation of markers of inter-neuronal damage (e.g., , Neurocan, and Brevican) among responders with PTSD that were thought to be downregulated because of their increased cerebral absorption ( Kuan et al, 2020 ; Waszczuk et al, 2023 ). Similarly, studies have noted that PTSD is associated with changes to glucocorticoid activation via activation of the FKBP5 gene ( Kuan et al, 2017 , 2019 ), a result that could downregulate glia ( Nichols et al, 2005 ).…”
Section: Discussionmentioning
confidence: 98%
“…Yet, GFAP levels could be significantly reduced in individuals with other neuropathologies specifically because GFAP might be binding directly to the cerebrum thereby avoiding being sloughed into the blood ( Pereira et al, 2021 ). A prior study of WTC responders with PTSD and mild cognitive impairment found downregulation of markers of inter-neuronal damage (e.g., , Neurocan, and Brevican) among responders with PTSD that were thought to be downregulated because of their increased cerebral absorption ( Kuan et al, 2020 ; Waszczuk et al, 2023 ). Similarly, studies have noted that PTSD is associated with changes to glucocorticoid activation via activation of the FKBP5 gene ( Kuan et al, 2017 , 2019 ), a result that could downregulate glia ( Nichols et al, 2005 ).…”
Section: Discussionmentioning
confidence: 98%
“…The top-gene, KANSL1, was significant in all cell types. Given previously reported associations between blood-based protein levels and PTSD, 38,39 we performed protein quantitative trait loci (pQTL) SMR 36 analysis for PTSD using data from the UK Biobank Pharma Proteomics Project 40 (N=54,306 samples and N=1,209 proteins). We identified 16 genes within 9 loci whose protein levels were significantly associated with PTSD (p<0.05/1,209 and p HEIDI > 0.05) (Fig.…”
Section: Multi-omic Investigation Of Ptsdmentioning
confidence: 99%